Stalins Kommandotruppen 1941-1944 : Die ukrainischen Partisanenformationen - Gogun, Alexander (Ibidem-Verlag, 2015)
There are certain parallels between the operations Vladimir Putin initiated in the wake of the Ukraine crisis of 2014 and the approach Stalin took in the region during the Second World War. Stalin's ruthless use of scorched earth tactics, the deliberate provocation of reprisals of the occupiers against the civilian population, the destruction of their own villages, the chaotic collection of taxes in kind from the population, accompanied by everyday looting, benders, fornication and violence, fratricidal internal conflicts, the use of doping, the operational use of bacteriological weapons, and e.